The elusive role of NbLi bound polaron energy in hopping charge transport in Fe: LiNbO3. (23rd February 2018) - Guilbert, Laurent; Vittadello, Laura; Bazzan, Marco; Mhaouech, Imed; Messerschmidt, Simon; Imlau, Mirco
Abstract: Charge transport due to small polarons hopping among defective (bound polarons) and regular (free polarons) sites is shown to depend in a non-trivial way on the value of the stabilization energy provided by the lattice distortion surrounding the charge carriers. This energy, normally not directly accessible for bound polarons using spectroscopic techniques, is determined here by a combination of experimental and numerical methods for the important case of small electron polarons bound to N b L i defects in the prototype ferroelectric oxide lithium niobate. Our findings provide an estimation of the N b L i polaron stabilization energy E G P = ( 0.75 ± 0.05 )   e V and demonstrate that in lithium niobate both free and bound polarons contribute to charge transport at room temperature, explaining the fast decay of the light-induced bound polaron population observed by transient absorption spectroscopy.